PROFIL FAKTOR RISIKO YANG DAPAT DIMODIFIKASI PADA KASUS STROKE BERULANG DI RSUD ARIFIN ACHMAD PROVINSI RIAU - Irdelia, Ririe Rasky; Joko, Agus Tri; Bebasari, Eka (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Stroke is a disease which is the third leading cause of death in the world withgreat morbidity and mortality that can cause disability. Prevalence of stroke inIndonesia reached 8.3 of 1000 population. It is estimated that 5-14 % incidence ofstroke will be repeated in five years. This study is a retrospective descriptive studyusing total sampling method to determine the profile of modifiable risk factors inrecurrent stroke cases at Arifin Achmad General Hospital in Riau Province. Sampleswere obtained as many as 62 people were taken from medical records in the medicalrecord installation Arifin Achmad General Hospital in Riau Province in 2011-2012.The results showed that the prevalence of recurrent stroke cases in Arifin AchmadGeneral Hospital in Riau Province was 62 cases (8.05%). Distribution for riskfactors of hypertension were 57 people (91.94%), without diabetes were 39 people(62.90%), with dyslipidemia as risk factor were 46 people (95.83%), without heartdisease were 43 people (69.35%), 10 people (52.63%) were non-smokers, andpatients who did not consume alcohol were 17 people (89.47%). Recurrent strokecases with more than one risk factor were 48 people (77.42%). Patients whoundergone teraphy for hypertension were 30 people (52.63%), treatment for diabeteswere 6 people (50.00%), treatment for dyslipidemia were 2 people (4.35%), andtreatment for heart disease were 15 people (78.95%).Keywords: Stroke, recurrent stroke, risk factors